Palak variety Thar Hariparna for abiotic stressed hot arid climate - Samadia, D K; Verma, A K; Ram, Hanuman; Gurjar, P S (Indian Horticulture, 2022)
Among the leafy vegetables, palak (Beta vulgaris var. bengalensis Roxb) is the most adaptive plant but was not much exploited for developing better yielding genotypes suited to the abiotic stressed production sites. Its tender leaves are used extensively in both fresh and dehydrated forms. Thar Hariparna is developed through selection from native population of palak with better plant growth and bigger leaf size. It is recommended by ICAR-CIAH, Bikaner for October sowing and leaf harvesting from November to March under hot arid climate. Light green–darkgreen colour leaves are big, glossy, smooth, thick, soft and juicy. It yields high quality marketable leaves (154.72 q/ha) in sandy soils with pH range 8.0-8.5. Quality seed production is profitable.